"Evaluation of the effect of roasted lentil flour (lentil savigh) as a functional food in menstrual bleeding reduction". (June 2019) - Shafiee, Malihe; Heidari, Akram; Amouzegar, Hora; Khani, Samira; Nojavan, Fatemeh
Highlights: Due to prevalence of menorrhagia and dissatisfaction of treatment in some cases, this study examined the effects of roasted lentil flour as a food supplement in treatment of heavy menstrual bleeding. Roasted lentil flour (lentil savigh) was effective in menstrual bleeding reduction and improving the quality of life in women suffering from menorrhagia, So "lentil savigh ", as a functional food, could be introduced as a good initial choice for menorrhagia treatment or a supplementary. Abstract: Background: Menorrhagia is a regular menstrual cycle lasting more than seven days and/or blood loss over 80 mL per cycle. One of the herbs recommended in Iranian traditional medicine for menorrhagia treatment is lentil savigh, which is the flour made from roasted lentil ( Lens culinaris medic ). Methods: The current randomized clinical trial was conducted on 54 patients within the age range of 18 to 50 years randomly divided into two groups. The treatment group took three 10-gram lentil savigh sachets in the morning. The control group was treated with 500 mg tranexamic acid capsule every eight hours, both from the first day of menstruation for seven days. Patient's bleeding was evaluated by the pictorial blood loss assessment chart (PBAC), before and in each of the three treatment cycles. Quality of life was evaluated by the menorrhagia questionnaire (MQ) at the beginning and the end of the study for each patient. Results: The mean (SD) of PBAC scores significantly decreased before and after three cycles from 383.5(163) to 222.1(128.6) in the lentil savigh group (P < 0.0001), and from 333.8(141.3) to 239.1(132.6) in the tranexamic acid group (P < 0.0001). There was no significant difference between the two groups (P < 0.6). Quality of life significantly improved in the lentil savigh group from 61.5(12.3) to 34.4(14.6) in comparison with that of the tranexamic acid group changing from 56.3(11.1) to 46.8(12.7) (P < 0.004). Conclusion: Both products were effective in menstrual bleeding reduction, but lentil savigh improved the quality of life more effectively. Therefore, lentil savigh, as a functional food, could be introduced as a good initial choice for menorrhagia treatment.